PSIX-7 Differences in rumen degradability according to the degree of corn gelatinization. (8th October 2021) - Shin, Ji Yun; Woo, Junsik; Ryu, Gyeonglim; Oh, Young Kyoon; Park, Keun Kyu
Abstract: This study was conducted to evaluate the difference in ruminal degradability by the degree of gelatinization of corn grain. The treatments were Control (whole corn grain), T1 (70% gelatinized corn grain steam flake), and T2 (30% gelatinized corn grain steam flake). Corn grain steam flaked for T1 was produced by a pressurized steam chamber for a longer time than T2. For this reason, the thickness of T1 and T2 was 1.5 and 2.5mm on average, respectively. Two Holstein cows (BW.405±15.4kg, 26.5±12 months) fitted with ruminal cannula were fed 4 kg of tall fescue and 3 kg of a formulated concentrate mix. Immediately after morning feeding, the nylon bags containing the sample from all treatments were incubated in the ruminal ventral sac for 0, 2, 4, 8, 12, 18, 24, 36, and 48h. At 0h of incubation, the DM degradability of T1 (16.70%) was higher (P< 0.05) than Control (9.74%) and T2 (12.00%). The degradability of both Control and T2 slightly increased from 4 (23.08 and 27.57%) to 18h (36.65 and 35.52%), exponentially increased from 18 to 48h. On the other hand, the degradability for T1 exponentially increased from 2 (28.74%) to 18h (77.31%), only slightly increased thereafter. The final degradability (48h) of Control, T1, and T2 were 78.07, 89.20, and 84.86%, respectively (P< 0.05). The fraction a of DM degradability for T1 (24.29%) was higher than Control (2.26%) and T2 (6.26%) (P< 0.05). The effective degradability (ED) of T1 (75.31%) was higher (P< 0.05) than Control (57.42%) and T2 (60.86%). Therefore, this study demonstrated that 70% gelatinized corn grain steam flake showed a higher rate of ruminal degradability than other treatments. Thus, it is necessary to determine how these differences affect ruminant productivity through additional feeding experiments.